Bibliometric analysis of blockchain technology in risk management - Alsulaimani, Haneen; Alzahrani, Saeed (Edelweiss Applied Science and Technology, 2025)
This study presents a bibliometric analysis of the literature exploring the development and application of blockchain technology in risk management from 2020 to 2024. It highlights blockchain’s transformative role across key sectors, including supply chain management, cybersecurity, financial services, and healthcare. Data visualization, conducted using VOSviewer, identifies significant trends, influential authors, and key research areas that drive the integration of blockchain in mitigating complex risks and serving as a viable solution. The findings reveal that integrating blockchain with advanced technologies such as artificial intelligence (AI) and the Internet of Things (IoT) enhances its capacity to offer transparency, security, and efficiency. The analysis shows a notable increase in research activity beginning in 2021, with cybersecurity and supply chain management emerging as primary focus areas. Additionally, recent years have seen growing interest in applying blockchain to financial services and healthcare, reflecting its expanding role across various sectors. Overall, the results highlight blockchain’s potential to reshape risk management practices by enabling more transparent, secure, and adaptive systems. This research offers valuable insights for policymakers, industry leaders, and academics seeking to leverage blockchain in building resilient and future-ready risk management frameworks.